KONSEP PENDIDIKAN IBNU KHALDUN DAN RELEVANSI PENDIDIKAN DI ERA MODERN - Muhammad Ersyad Anshari; Rahma Dona, Fathiyyah Putri Pasaribu, Wedra Aprison (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
Islamic education today still needs efforts to support the growth and development of the development of Islamic education. One of the efforts made by photographing the condition of the development of Islamic education in the era of the glory of the Islamic era so that many gave birth to great figures of Islam along with his monumental work. The current condition of the science of Islamic education which experiences various kinds of problems needs to be addressed immediately by developing the science of Islamic education through a series of research studies involving the study of Muslim intellectual figures from the classical, mid-to modern times. One of the figures who took part in the world of Islamic philosophers was Ibn Khaldun who had produced many works and their existence in the scientific field.